Personalized Nutrition for Obesity Management: A Mini-Review - Michael T. Okafor (International Journal of Medicine and Health Development)
Obesity is a pro-inflammatory state and a chronic health condition, which falls within the spectrum of immune-mediated inflammatory diseases (IMIDs). It is caused mainly by the consumption of excess calories and egregious food substances. A Personalized Food Avoidance Dietary Approach for Management of IMIDs (PFA-DAMI) addresses primary and secondary immune intolerances of different individuals to dietary constituents. Exposure to toxic food substances is responsible for inflammatory immune dysfunction that mediates obesity. Hence, a PFA-DAMI is promising for the management of obesity. T cell dysfunction disease mediating models describing inflammatory disease processes underlying IMIDs exist. However, they do not highlight inflammatory processes underlying the diseases concerning toxin-mediated epigenetic T cell dysfunction. Online searches were conducted on databases, such as Google Scholar, PubMed, Biomed Central, and SciELO. Articles were reviewed using keywords, such as obesity, personalized nutrition, immune optimization/dysfunction, T lymphocyte activation/dysfunction, cytokines, and adipokines. There is a putative T cell toxin-mediated dysfunction disease model for IMIDs, which may apply to other diseases. The putative disease model may highlight the actual inflammatory immune dysfunctional processes underlying T cell disease mediation in inflammatory diseases, which may be validated by multiomic studies. Validation of the putative disease model using obesity as an example should pave the way for a better understanding of the role of personalized nutrition in obesity management.